STUDI ON APLICATION OF HOUSE OF QUALITY (HOQ) TO IMPROVE THE QUALITY OF HEALTH CARE : Case Study in GMC Health Center Yogyakarta - Yurista Septiani Dewi; Achmad Purnomo; Edi Prasetyo Nugroho (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
GMC is an organization that provided health assurance for academicians in UGM. As a health assurance, GMC should increase their quality. Quality Function Deployment (QFD) is a part of Total Quality Management (TQM) tool that can use for measure TQM by House of Quality (HOQ) design. The aim of this study is to analyze the implementation of HOQ. This study located in GMC Health Center of Yogyakarta. The research was conducted using 2 samples. The samples consist of 2, 100 external customers and 10 internal customers, amounting to 10. This research followed by interviews with top managers to build house of Quality. And then build house of quality, finally analyze the atribute that must be repaired by management of GMC. The results showed that there were three aspects that should be prioritized by GMC. The first aspect is pharmaceutical care that included 4 attributes. The highest gap of this aspect completeness of drug supplies 6.21 and the availability of a pharmacist that was consumer value answered by the management GMC with the high level of difficulty. From the relative weight score 106.61 percent can be showed that the availability of pharmacist has the highest value on the customer excpectations for this aspects.The other aspects that must be improved are the emphaty and responsiveness and time. Emphaty dimension has the the highest value of technical descriptors 538.397 that can be done by the GMC for complete customer expectations in all aspects. Systemic obstacle for implement the House of Quality were financial and human resources. Keywords: Service Quality, Total Quality Management, Quality Function Deployment, House Of Quality